1972
DOI: 10.1042/bj1291085
|View full text |Cite
|
Sign up to set email alerts
|

Purine ribonucleotide biosynthesis, interconversion and catabolism in mouse brain in vitro

Abstract: The relative rates of the synthetic, interconversion and catabolic reactions of purine metabolism in chopped mouse cerebrum were studied. The rates of incorporation of [(14)C]adenine and [(14)C]hypoxanthine into purine ribonucleotides were much less than the potential activities of adenine phosphoribosyltransferase and hypoxanthine phosphoribosyltransferase, and the rates of incorporation were stimulated by the addition of guanosine to the incubation mixture. The availability of ribose phosphates may be a limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
1

Year Published

1977
1977
2001
2001

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 27 publications
5
9
1
Order By: Relevance
“…In the control glia cells, the different metabolic fate of hypoxanthine from that of guanine probably reflects also the absence of xanthine oxidase (xanthine : oxygen oxidoreductase ; EC 1.3.2.3) activity (Zoref‐Shani et al, 1995). Similar results concerning the fate of hypoxanthine and guanine in the control and HGPRT‐deficient glia were obtained in our laboratory before in neurons (Brosh et al, 1992 ; Zoref‐Shani et al, 1993), and by others in whole brain tissue (Wong and Henderson, 1972). These results are also compatible with findings concerning the content of hypoxanthine and xanthine in the CSF of boys affected with LNS (Rosenbloom et al, 1967 ; Sweetman, 1968 ; Harkness et al, 1988).…”
Section: Discussionsupporting
confidence: 85%
“…In the control glia cells, the different metabolic fate of hypoxanthine from that of guanine probably reflects also the absence of xanthine oxidase (xanthine : oxygen oxidoreductase ; EC 1.3.2.3) activity (Zoref‐Shani et al, 1995). Similar results concerning the fate of hypoxanthine and guanine in the control and HGPRT‐deficient glia were obtained in our laboratory before in neurons (Brosh et al, 1992 ; Zoref‐Shani et al, 1993), and by others in whole brain tissue (Wong and Henderson, 1972). These results are also compatible with findings concerning the content of hypoxanthine and xanthine in the CSF of boys affected with LNS (Rosenbloom et al, 1967 ; Sweetman, 1968 ; Harkness et al, 1988).…”
Section: Discussionsupporting
confidence: 85%
“…In release experiments, hypoxanthine was the predominant moiety released from the isolated choroid plexus, although some inosine was also released (Table 4). It is worth noting that rat and rabbit brain slices can also concentrate hypoxanthine and metabolize it to nucleotides (Santos et al, 1968;Wong and Henderson, 1972). After rabbit brain slices were incubated in [I4Cjhypoxanthine, both [14C]hypoxanthine and, to a much a smaller extent, [I4C]inosine were released (R. Spector, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Betz has recently shown that the small amounts of xanthine oxidase present in brain are concentrated in the cerebral capillaries (Betz, 1985). However, the possibility that cerebral capillaries form large amounts of xanthine and uric acid in vivo from hypoxanthine is not consistent with the finding that brain slices convert >90% of the accumulated [ I4C]hypoxanthine to nucleotides and <lo% is converted to [14C]xanthine and [14C]uric acid (Santos et al, 1968;Wong and Henderson, 1972). We suggest that the minimal formation of [14C]uric acid and ['4C]allantoin in the CNS from [I4C]hypoxanthine in vivo is consistent with the very high and very low concentrations of HGPRTase and xanthine oxidase respectively in brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike adenine, guanine, formed both intra-and extracellularly by the degradation of GBPs, is not recycled back into nucleosides and nucleotides to any great extent (Wong and Henderson, 1972). This is because in brain, the activity of guanase is higher than that of phosphorybosyltransferase (PRT), the enzyme catalysing salvage nucleotide synthesis ( Fig.…”
Section: Extracellular Metabolismmentioning
confidence: 99%